Myb10‐D confers PHS‐3D resistance to pre‐harvest sprouting by regulating NCED in ABA biosynthesis pathway of wheat. Issue 5 (30th March 2021) - Lang, Jing; Fu, Yuxin; Zhou, Yong; Cheng, Mengping; Deng, Min; Li, Maolian; Zhu, Tingting; Yang, Jian; Guo, Xiaojiang; Gui, Lixuan; Li, Linchuan; Chen, Zhongxu; et al.
Summary: Pre‐harvest sprouting (PHS), the germination of grain before harvest, is a serious problem resulting in wheat yield and quality losses. Here, we mapped the PHS resistance gene PHS‐3D from synthetic hexaploid wheat to a 2.4 Mb presence–absence variation (PAV) region and found that its resistance effect was attributed to the pleiotropic Myb10‐D by integrated omics and functional analyses. Three haplotypes were detected in this PAV region among 262 worldwide wheat lines and 16 Aegilops tauschii, and the germination percentages of wheat lines containing Myb10‐D was approximately 40% lower than that of the other lines. Transcriptome and metabolome profiling indicated that Myb10‐D affected the transcription of genes in both the flavonoid and abscisic acid (ABA) biosynthesis pathways, which resulted in increases in flavonoids and ABA in transgenic wheat lines. Myb10‐D activates 9‐ cis ‐epoxycarotenoid dioxygenase ( NCED ) by biding the secondary wall MYB‐responsive element (SMRE) to promote ABA biosynthesis in early wheat seed development stages. We revealed that the newly discovered function of Myb10‐D confers PHS resistance by enhancing ABA biosynthesis to delay germination in wheat. The PAV harboring Myb10‐D associated with grain color and PHS will be useful for understanding and selecting white grained PHS resistant wheat cultivars.